Emerging Africa : how the global economy's 'last frontier' can prosper and matter - Moghalu, Kingsley Chiedu (Ibadan : Bookcraft, 2013)
"In this important book, Moghalu challenges conventional wisdoms about Africa's quest for economic growth in a globalized world. Drawing on philosophy, economics and strategy, his argument covers a range of subjects, from capitalism to transformation agendas, finance to foreign investment, and from innovation and human capital to world trade. Ultimately he demonstrates how Africa's progress in the 21st century will require nothing short of the reinvention of the African mindset"--Publisher description.
Includes bibliographical references and index.
oif 18/09/14
Loan
Keywords: Economic development; Investments, Foreign; Africa